Arab reception of postcolonial criticism: Arab reception of postcolonial criticism (Journal of Hama University, 2025)
This research seeks to present the Arab reception of post-colonial criticism. Post-colonial discourse is represented by the evocation of Third World cultures in the Western academic space, through the pioneers of this theory who reformulated it with inspiration from the cultures of their original countries, recalling their history. Western hegemony has been the subject of frameworks. Several research and epistemological questions were raised, and the problem of the research is determined by the fact that it deals with the Arab reception of post-colonial criticism, while the objectives of the research stem from the desire to criticize the Arab reception of post-colonial criticism. The research followed the descriptive and analytical approach, and it reached many results. Perhaps the most notable are: Post-colonial criticism did not have the desired effect. Rather, most of the Arab reception remained circling around the personality of Edward Said and his opinions on many contemporary issues more than it addressed post-colonial criticism. Perhaps the weakness of Edward Said’s influence in the Arab world is due to the focus of Arab readers. On the ideological side of his views; Therefore, Edward Said’s thought did not contribute to creating a critical, cognitive perspective that includes the ideological horizon and does not start from it. Perhaps the reason is that Edward Said’s critical determinants require cognitive digging into the foundational structures of his thought before criticizing it, as this thought is what generated this criticism.
Keywords: criticism, postcolonialism, Edward Said